Game Edukasi Pembelajaran Aksara Jawa Menggunakan Teknologi Augmented Reality Berbasis Android di SD Negeri Sinomwidodo Tambakromo Pati - Gumiwang, Dimas Putu; Windasari, Ike Pertiwi; Septiana, Risma (Jurnal Ilmu Teknik dan Komputer, 2022)
Java Island is one of the regions in Indonesia that has a variety of cultures, one of which is the Javanese script. Javanese script or better known as Hanacaraka or Carakan is a noble cultural heritage of the Indonesian nation, namely the Javanese tribe which has a license and has been officially recognized by UNESCO. Although it has received recognition by UNESCO, it does not necessarily cause Javanese script to be known and in demand by many people. Elementary school students are expected to have the skills to read and write Javanese script to preserve Javanese script. Many elementary school students think that the material for Javanese script is quite difficult, because it is new material, considering that elementary school-aged children are new to the alphabet and do not know other letters, such as Javanese script. The use of Javanese script learning media at SD Negeri Sinomwidodo itself is currently still lacking, namely still using printed media such as textbooks, student activity sheets, Javanese language and writing on the blackboard which looks less attractive to students. From these problems, a solution was obtained to create an educational game of Javanese script using augmented reality technology. The purpose of making this game is to provide learning about Javanese script through educational games for students of SD Negeri Sinomwidodo. This educational game of Javanese script was designed using the game engine unity and developed using the MDLC (Multimedia Development Life Cycle) method. The development of this method is carried out based on six stages, namely concept, design, material collection, assembly, testing and distribution. According to Luther in Binanto, these six stages do not have to be sequential in practice, these stages can exchange positions with each other. Even so, the concept stage should be the first thing to do. This educational game of Javanese script was tested using 3 tests, namely black box, usability and pre-test and post-test. Based on the results of the study, the results of black box testing can run smoothly according to the expected function. In usability testing, the overall average score is 90.60% in terms of usability, convenience and satisfaction in using this game and getting a sig value. (2-tailed) of 0.003 on the paired sample t test method, which means it can have a significant effect, which means this game can have an effect on increasing understanding of Javanese script in SD Negeri Sinomwidodo.